Optimising elevator group performance with adaptive objective function - Glad, Anton (My University, 2021)
An elevator group consists of elevators and an elevator group controller. The controller decides which elevator to allocate to a call given by a passenger. The allocation can be decided with mathematical optimisation by minimising an objective function. Different objectives can be used in such a function, and their relative importance can be adjusted with weight coefficients. It is known, that by using different weight coefficients for different traffic situations, the performance of the elevator group can be improved. However, the exact relationship between the weight coefficient and the traffic is not known. The aim of this thesis is to study this relationship and implement a method that utilises this information. Two methods are designed and implemented in this study. The first method, an offline method, uses generated data of the traffic. Different traffic situations were simulated with different traffic intensities and weight coefficients. Then, a sigmoid function was fitted to the data of which weight coefficient resulted in the lowest average waiting time per traffic intensity. This function could then be used in the elevator group controller to adjust the weight coefficient according to the traffic intensity. In addition, to improve the results the traffic intensity was estimated from the number of waiting passengers. The second method, an online method, uses a reinforcement learning algorithm. The algorithm learned a similar mapping between the traffic intensity and the best weight coefficient during the elevator use. The analysis showed that the optimal weight coefficient does not only depend on the traffic intensity, but also on the traffic type. The results showed that changing the weight coefficient adaptively according to the traffic intensity decreased the average waiting times, lobby queue length and the number of long waiting times and increased the handling capacity of the system compared to previous methods. One of the previous methods uses hand-tuned parameters and does not estimate the traffic intensity. This study showed that the results can be improved with data-fitted parameters and an estimation for the traffic intensity. Reinforcement learning is also a noteworthy approach for adjusting the weight coefficient, however its implementation needs further research in order for it to work better. The conclusion of the study is that in order to improve the elevator group's performance, adaptive weight coefficient can be used. The adaptivity should be based on at least the traffic intensity, but if possible, also on the traffic direction. Reinforcement learning-based approach needs more research, but it is a noteworthy approach for implementing an adaptive weight coefficient without any preliminary simulations.

Hissiryhmä koostuu hisseistä sekä hissiryhmäohjaimesta. Hissiryhmäohjain päättää, mikä hissi allokoidaan kullekkin matkustajan antamalle kutsulle. Allokaatio voidaan päättää matemaattista optimointia hyödyntämällä minimoimalla tavoitefunktion arvoa. Tavoitefunktio voi koostua eri tavoitteista ja niiden suhteellista tärkeyttä voidaan säätää painokertoimilla. Hissiryhmän suorituskykyä voidaan parantaa käyttämällä eri painokertoimia eri liikennetilanteissa. Tosin ei ole tiedossa, kuinka kyseisiä painokertoimia tulee tarkalleen säätää. Tämän opinnäytteen tarkoituksena on tutkia tätä yhteyttä liikenteen ja optimaalisten painokertoimien välillä, ja toteuttaa tätä tietoa hyödyntävä menetelmä. Tässä opinnäytteessä suunniteltiin ja toteutettiin kaksi menetelmää. Ensimmäinen menetelmä, jota kutsutaan "offline"-menetelmäksi, käyttää simuloimalla tuotettua liikennedataa. Eri liikennetilanteita simuloitiin käyttämällä eri painokertoimia ja liikenneintensiteettejä. Datasta laskettiin, mitkä painokertoimet tuottivat alhaisimmat matkustajien odotusajat eri liikenteen intensiteeteillä. Tähän sovitettiin sigmoid-funktio. Sovitettua funktiota apuna käyttäen hissiryhmäohjain pystyy vaihtamaan painokerrointa liikenteen intensiteetin mukaan. Lisäksi tulosten parantamiseksi aikaisempiin menetelmiin verrattuna liikenteen intensiteetti arvioitiin odottavien matkustajien lukumäärästä. Toinen menetelmä, jota kutsutaan "online"-menetelmäksi, käyttää vahvistusoppimisalgoritmia. Algoritmi oppi hissien käytön aikana samanlaisen kuvauksen liikenteen intensiteetin ja parhaan painokertoimen välillä. Tutkimuksen analyysin mukaan optimaalinen painokerroin riippuu sekä liikenteen intensiteetistä että liikenteen tyypistä. Tulokset osoittivat, että painokertoimen vaihtaminen adaptiivisesti liikenneintensiteetin mukaan vähensi keskimääräisiä odotusaikoja, aulan jonon pituutta sekä pitkien odotusaikojen määrää ja paransi hissien kuljetuskapasiteettia aikaisempiin menetelmiin verrattuna. Eräs aiemmin tutkittu menetelmä käytti silmämääräisesti säädettyjä parametreja, eikä se käyttänyt liikenneintensiteetin arviota. Tämä tutkimus osoitti, että tuloksia voidaan parantaa dataan sovitetuilla parametreilla ja arviolla liikenteen intensiteetille. Vahvistusoppiminen on myös varteenotettava lähestymistapa painokertoimen säätämiseksi, mutta sen toteutus tarvitsee lisää tutkimusta tulosten parantamiseksi. Opinnäytteen lopputulos on, että adaptiivista painokerrointa voidaan käyttää hissiryhmän suorituskyvyn parantamiseksi. Adaptiivisuus tulisi määrittää ainakin liikenteen intensiteetin perusteella, mutta jos mahdollista, myös liikenteen suunnan perusteella. Adaptiivinen painokerroin, joka ei tarvitse alustavia simulaatioita, voidaan toteuttaa käyttämällä vahvistusoppimismenetelmää. Kyseinen menetelmä tarvitsee kuitenkin vielä lisätutkimusta.
Keywords: Elevator group control, multi-objective optimisation, adaptive weight coefficient, call allocation, simulation, reinforcement learning, traffic estimation